Study on Crack Evolution and Failure Mechanism of Fully Penetrated Fracture Grouting Body. (10th October 2022) - Wang, Hanqing; Li, Li; Li, Xinwang; Cheng, Lichao; Shen, Pengfei
Abstract : Grouting is a common method used in reinforcing fractured rock, and it is important to study the crack evolution and mechanical properties of fractured rock after grouting under the influence of different excavation rates and crack geometries. Therefore, a set of grouting molds for small-sized specimens with fully penetrated cracks were designed. The crack formation location and penetration mechanism of grouted bodies with different crack inclinations using uniaxial compression tests with different loading rates were investigated. The crack extension process and energy concentration areas of the grouted plus solid specimens at different stages were revealed from the acoustic characteristic. The results show that the peak strength of crack-grouting sandstone decreases with the increase of crack inclination under the same loading rate. Comparisons of the crack inclination in slurry specimens under different loading rates imply that there is a critical value of crack inclination at 45° which concentrates the damage and cracking of the grouted body under compression within the grouted solidified body. When the crack inclination is small, the specimen is mainly extended from the crack of the rock block at the upper end of the grout consolidation to the lower end of the crack surface, and the acoustic emission ring count data mainly show a rising trend throughout the whole process, when the crack inclination is large, cracks are mainly produced around the surface subjected to grout consolidation and gradually expand to the interior of the grouted body, and there is almost zero growth in the ringing count in the elastic stage (II) and a larger growth in the ringing count in the yielding stage (III) and postpeak stage (IV). This research work can provide disaster prediction and theoretical guidance for the corresponding engineering construction of crack-grouting sandstone.